Formative Assessment of Social-Emotional Skills Using Rubrics: A Review of Knowns and Unknowns - Pancorbo, Gina; Primi, Ricardo; John, Oliver P.; Santos, Daniel; De Fruyt, Filip (Frontiers in Education, 2021)
Educational practitioners have been increasingly interested in the use of formative assessment and rubrics to develop social-emotional skills in children and adolescents. Although social-emotional rubrics are nowadays commonly used, a thorough evaluation of their psychometric properties has not been conducted. In this scoping review, we examine the knowns and unknowns of the use of formative assessment approaches and rubrics in social-emotional learning. We first review initiatives of formative assessment and development of rubrics to assess social-emotional skills. Then, we discuss challenges associated with the development and use of rubrics to evaluate social-emotional skills in youth focusing on 1) assessment of single skills versus assessment of a comprehensive taxonomy of skills; 2) developing rubrics’ performance level descriptions that accurately describe increasing mastery of skills; 3) obtaining adequate internal consistency and discriminant validity evidence; 4) self-reports versus observer reports of skills; and finally 5) how to account for adolescents’ development in the construction of rubrics. This review outlines a research agenda for the psychometric study of rubrics to be used in social-emotional skill assessment.